Water conservancy monitoring based on visual sensor networks. (June 2018) - Jia, Kebin; Wei, Zhihao
Aiming at the complexity of the network transmission environment and the decentralization of the monitoring sites in the middle route of the South to North Water Diversion Project, this article presents a water conservancy monitoring architecture based on the visual sensor networks. First, a network assessment method is proposed to evaluate the sensor networks condition, and the encoder is adjusted with the result of the sensor networks condition evaluation. Then, based on distributed database architecture and visualization system construction, a three-level structure of the water conservancy monitoring system is designed and built. The experiment results show that the water conservancy monitoring system proposed in this article meets the transmission requirement under the complex sensor networks condition of water conservancy project. The water conservancy monitoring system has been applied to the middle route of the South to North Water Diversion Project, which achieves the needs of engineering applications.